2007
DOI: 10.1128/jcm.00838-07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Multiplexed PCR Assay for Detection of Respiratory Viral Pathogens in a Public Health Laboratory Setting

Abstract: There are numerous viral and bacterial causes of respiratory disease. To enable rapid and sensitive detection of even the most prevalent causes, there is a need for more-simplified testing systems that enable researchers and clinicians to perform multiplexed molecular diagnostics quickly and easily. To this end, a new multiplexed molecular test called the MultiCode-PLx respiratory virus panel (PLx-RVP) was developed and then implemented in a public health laboratory setting. A total of 687 respiratory samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…The two viruses which were associated with the largest numbers of discrepancies were RV and PIV. As was seen in the other evaluations (8,13,15), the PLx-RVP detected many more RVs than conventional testing. The presence of RV was confirmed in the large majority of the discrepant specimens by the reference PCR assay, supporting the enhanced sensitivity of PLx-RVP for RV.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The two viruses which were associated with the largest numbers of discrepancies were RV and PIV. As was seen in the other evaluations (8,13,15), the PLx-RVP detected many more RVs than conventional testing. The presence of RV was confirmed in the large majority of the discrepant specimens by the reference PCR assay, supporting the enhanced sensitivity of PLx-RVP for RV.…”
Section: Discussionsupporting
confidence: 73%
“…The newly developed multiplex molecular assays to detect respiratory viruses (12,13,15,16) are a major step forward in diagnostic virology. In the present study, we evaluated one such assay, the PLx-RVP, by comparing it to conventional virologic testing, consisting of FA staining and culture as performed in a routine diagnostic virology laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improved sensitivity of PCR over antigen testing and virus isolation for RSV (14,16,44,45) and influenza virus (17,20,40,41,48) has been previously demonstrated by uniplex, as well as multiplex, testing (4,23,28,32). Studies have also demonstrated improved sensitivity of PCR in combination with culture as a composite "gold standard" or as the alternate reference test for RSV or influenza virus (1,19,33,36,38).…”
Section: Resultsmentioning
confidence: 97%